Ontology and Gnoseology in Abelardo’s Logica ingredientibus - Castello Dubra, Julio A. (Anales del Seminario de Historia de la Filosofía, 2004)
The paper deals with the section of Peter Abaelard’s Glossae super Porphyrium concerning the three questions about the universals. The pars destruens, in which Abaelard criticizes the realistic doctrines of William of Champeaux, does not have a merely negative function, but it tries to reach the starting-point of Abaelard’s own position, namely, that things differ not only in their forms or accidents, but also in their matters or essences. When he speaks of the image of the universal term, he does not explain the process of the elaboration of the universal concept starting from the thing, but he rather refers to the intellectual signification of terms, in so far as they “produce intellections”. This default could be explained because of the fact that, in Abaelard’s view, the human intelligence hardly ever or never grasps the essences of things.